Pd(II)-Catalyzed Enantioselective γ-C(sp(3))−H Functionalizations of Free Cyclopropylmethylamines - Zhuang, Zhe (J Am Chem Soc, 2020)
Prized for their ability to reliably forge stereocenters with precise regiocontrol from simple and abundant starting materials, substrate-directable enantioselective reactions are widely used in modern organic synthesis. As such, enantioselective C(sp(3))−H functionalization reactions directed by innate functional groups could provide new routes to introduce molecular complexity within the inert hydrocarbon moiety, but so far this approach has been met with little success. While free primary aliphatic amines are common, versatile intermediates in synthesis, they are traditionally unreactive in C(sp(3))−H activation reactions. Herein we report the Pd-catalyzed enantioselective C(sp(3))−H functionalization of free aliphatic amines (cyclopropylmethylamines) enabled by a chiral bidentate thioether ligand. This ligand’s privileged bidentate coordination mode and thioether motif favor the generation of the requisite mono(amine)-Pd(II) intermediate, thus enabling the enantioselective C−H activation of free amines. The resulting C−Pd(II) species could engage in either Pd(II)/Pd(IV) or Pd(II)/Pd(0) catalytic cycles, enabling access to a diverse range of products through (hetero)arylation, carbonylation and olefination reactions. Consequently, this versatile reactivity offers medicinal chemists a general strategy to rapidly prepare and functionalize biologically relevant amines.